THE PHENOMENON OF MARRIAGE IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Kudeikina, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The marital relationship has been changing over time. The institution of marriage has become more democratic, following societal development. Marriage and divorce have lost their bureaucratic and moral obstacles. However, marriage has retained its role in the welfare of spouses and the evolution of society. Law protects the moral and economic rights of spouses. It should be noted, however, that the safeguarding of spouses’ rights and interests a priori concerns the rights and interests of third parties. This is the phenomenon of marriage. In a legal relationship, spouses are recognised as special right holders by default, which refers, for example, to insolvency proceedings, matrimonial property regimes and social rights. The research analyses the correlation between the trends of the institution of marriage and third-party rights in the context of the welfare of society. The objective of the research is to analyse the institution of marriage in order to trace its development in the modern world and establish how it affects third-party rights and public interests in general. The research employs methods of legal interpretation to analyse legislation and the inductive and deductive method to draw conclusions and formulate suggestions. Based on the results of the research, the institution of marriage is undergoing transformation. Marriage is losing its initial importance. Unmarried cohabitation is becoming increasingly prevalent. The biggest challenge is to balance the right to self-determination of a person choosing cohabitation and the public interest in legal stability and predictability, which are essential for the sustainable development of society.